2021
DOI: 10.3390/agronomy11061258
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship between Information-Seeking Behavior and Adoption of Biofertilizers among Onion Farmers

Abstract: Recently, there has been increasing concern about reducing and replacing chemical fertilizers with biofertilizers to enhance soil fertility and maintain agroecosystems and sustainable agricultural production. Given that knowledge of biofertilizers is information-intensive, the lack of information-seeking behavior (ISB) might be the primary constraint for farmers adopting biofertilizers. This study aimed to analyze how ISB influences farmers’ adoption of biofertilizers, using a sample of 228 onion farmers in Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Previous research has found that farmers’ information-gaining behavior, knowledge, and attitude toward innovation all influence technology adoption. However, the effectiveness of the adoption process is also dependent on the farmers’ trust in and access to information sources [ 61 , 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has found that farmers’ information-gaining behavior, knowledge, and attitude toward innovation all influence technology adoption. However, the effectiveness of the adoption process is also dependent on the farmers’ trust in and access to information sources [ 61 , 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, efforts to establish a comprehensive regulatory framework have been insufficient in many countries. For example, the number of colony-forming units (CFU) is the primary metric for quality assessment, yet a comprehensive regulatory framework is conspicuously lacking [26].…”
Section: Quality Controlmentioning
confidence: 99%
“…However, the adoption of biofertilizers remains limited, likely due to inappropriate formulations and a lack of quality control capacity in some regions [62]. It is crucial to conduct adequate research to promote the production of quality biofertilizers by implementing effective regulatory frameworks and providing adequate extension programs [26].…”
Section: Growing Awarenessmentioning
confidence: 99%
“…the preference for more traditional buying, and the push for digital solutions on the supplier side, fit together? Studies indicate the high degree of heterogeneity among farmers in their use of new information media (Fecke et al, 2018b;Kassem et al, 2021) as well as e-commerce (Ackermann et al, 2018;Ardrey et al, 2020;Fecke et al, 2018a;Schulze Schwering and Spiller, 2018).…”
Section: Introductionmentioning
confidence: 99%